Division of binary mixes by the combination of processes of fractional crystallization and fractional fusion - G. A. Nosov; A. A. Bessonov; V. V. Karasev (Тонкие химические технологии, 2009)
The theoretical analysis of division of binary mixes by a combination of processes of fractional crystallization and fractional fusion with recirculation manifold from a fusion stage on a crystallization stage is made.